Evaluation of the impact that will have on the economy of the Ecuador the start of production of the deposits of metallic materials - Soria Venegas, Francisco (2017)
The study is based on a mining legal and tax framework, economic studies, to evaluate the economic impact of starting the exploitation of the principal metallic mineral deposits of El Domo, Fruta del Norte, Loma Larga and Mirador in Ecuador. Moreover, it estimates the potential of the mining industry in Ecuador based on the certified information of the technical reports NI 43-101. In Ecuadorian territory, the Andes possess geologic conditions favorable for the formation of world class metallic mineral deposits. These physiological and geological characteristics are similar to the ones on all the South American Andean belt where neighboring countries such as Colombia, Peru, Bolivia, Argentina and Chile have successfully developed their mining industry. The methodology applied to evaluate the mineral deposits uses qualitative and quantitative variables globally accepted and it also offers recommendations for changes on the legal regime. Under the current legal regime there are three categories for the exploitation of mineral deposits: Small Operations Mining, with up to 300 tones/day on underground operations; Medium Operations Mining, with up to 1000 tones/day on underground operations and up to 2000 tones/day on open pit operations, and Large Operations Mining, with production larger than the limits set on the previously mentioned. As a result of the analysis, it is recommended that the limits of the production volumes should be increased for the three categories so that mining development and production becomes more attractive for investors and mining companies of all sizes. Based on the cash flow from the projects under analysis, the tax burden varies from 38% to 45%. Nevertheless, the Ministerio de Mineria (Mining Regulatory Agency) and industry consultant Wood Mackenzie (January, 2016) concludes that the tax burden is close to 27%. According to available NI 43-101 international documentation, Ecuador has 8.5 M oz. of gold and 19.2 M oz. of silver in Reserves and 23.8 M oz. of gold and 168.3 M oz. of silver in Resources. Reserves of 47 million pounds of copper; 41.334 million pounds of copper as a Resource and 865 million pounds of molybdenum as a Resource. The initial investment (CAPEX) for the 4 projects will add up to USD 2,123 M, in the mine construction phase, between the years 2017 and 2021. The direct employment demand in the same period will be of 4,140 employees, from which, 30% will correspond to technical and administrative staff and 70% to operators and field workers. Preferably, the working force will be local to the project area. Indirect employment will be assigned at a regional and national level. According to the studies, the mining methods to be used are defined as follows: in El Domo a combination of open pit and underground mining, in Fruta del Norte and Loma Larga as underground, and Mirador as open pit. The estimate Net Smelter Revenue (NSR) combined for the 4 projects will be USD 11,410 million, in 17 years of production. The estimated economic benefits for the state adding the 4 projects, including Royalty + income tax + profif- sharing + VAT, in 17 years of operations of the mines will be USD 2,063 million.